1890 Okla. Stat. 495, ch. 25, art. 47, § 3 - (:unkn) unknown (My University, 1890)
It shall be unlawful for any person within this Territory, to sell or give to any minor any of the arms or weapons designated in section one and two of this article (§ 1...pistol, revolver, bowie knife, dirk, dagger, slung-shot, sword cane, spear, metal knuckles, or any other kind of knife or instrument manufactured or sold for the purpose of defense except as in this article provided) (§ 2...pistol, revolver, bowie knife, dirk knife, loaded cane, billy, metal knuckles, or any other offensive or defensive weapon, except as in this article provided).
Keywords: TRANSFER - MINORS